Molecular docking of seagrass extracts: investigating the interaction with lipoate protein ligase from enhalus acoroides - Rochmat, Agus; Kamil, Kintan NR; Syawalia, Nabila R; Yulvianti, Meri; Bukhari, Ahmad; Hariri, Ahmad; Suaedah, Suaedah; Ganiadi, Mochamad (Jurnal Teknika, 2024)
Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis and has become a serious global health issue due to increasing antibiotic resistance. Genetic variations in this bacterium enable the emergence of drug-resistant strains, necessitating the search for more effective alternative therapies. This study evaluates the potential of Enhalus acoroides metabolites as inhibitors of the Lipoate Protein Ligase (LipB) enzyme, which plays a crucial role in the fatty acid synthesis of M. tuberculosis. The research was conducted through in silico analysis, including Lipinski's Rule of Five screening, ADMET pharmacokinetic modeling, compound identification using GC-MS, and molecular docking using PyRx, with interaction analysis performed via Biovia Studio. Three tested compounds—Lanosterol, N,N'-1,4-phenylenebis Benzamide, and Astragalin—exhibited significant binding affinity to the 1W66 receptor, with binding energies of -7.5 kcal/mol, -6.8 kcal/mol, and -7.8 kcal/mol, respectively. These values surpass those of the positive controls, Rifampicin (-7.0 kcal/mol) and Streptomycin (-6.5 kcal/mol), indicating the potential of these compounds as new anti-TB drug candidates. This study confirms that Enhalus acoroides metabolites have therapeutic potential in TB treatment, particularly in addressing antibiotic resistance. Further in vitro and in vivo studies are required to validate their pharmacological efficacy.TRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian //  TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//